A timeless vision - Niles, Kathryn M., author; Dormer, James T., advisor; Ellerby, David A., committee member; Mitchell, Carol A., committee member; Simons, Stephen R., committee member (Colorado State University. Libraries, 1996)
Landscape and figure are timeless, universal, and venerable motifs that compel constant and continued examination. This group of works employs form, movement, and spatial relations that are elements evident in both themes. I approach my subjects with a history of memories, an awareness of my surroundings, and my psychological state at the moment. These portrayals of life as I experience it may, in a sense, all be seen as self-portraits.
Keywords: Intaglio printing; Lithography